Neonatal Presentation of Rhizomelic Chondrodysplasia Punctata: Spot Diagnosis and Myriads of Unmet Needs - Prasad, Amarendra; Kumar, Chanchal; Shedabale, Dhiraj Sidagonda; Alam, Mohammad Shahbaz; Chand, Suvas; Romana, Ayesha (Dubai Medical Journal, 2025)
Background: Rhizomelic chondrodysplasia punctata (RCDP) is an uncommon inborn error of metabolism related to peroxisome. The inheritance pattern of this problem is autosomal recessive in nature. Five genetic subtypes have been reported which are clinically indistinguishable. Majority of cases have arthrogryposis, cataract, and significant growth and neurodevelopmental impairments. Diagnosis is made by observing skeletal changes, cataract, and biochemical changes of peroxisomal dysfunction, including raised phytanic acid and reduced red cell plasmalogen level, and is confirmed by genetic analysis. The mainstay of treatment is supportive measures. Case Report: We present a term male neonate born with cataract and bilateral contracture at hip, knee, elbow, and wrist. Skeletal radiographs suggested shortening of proximal long bones of the limbs (both humerus and femur) as compared to distal long bones (suggesting rhizomelia) and asymmetric multiple punctate calcifications in epiphyseal regions of femur and humerus. Conclusion: A multidisciplinary approach including neonatology/pediatrics, pediatric neurology, ophthalmology, physical and occupational therapy, cardiology, and pediatric orthopedic services would bring about optimal results for the infant and the family. The use of genetic epidemiological approaches to compute the struggles of individuals affected with this disorder will help in understanding their unmet medical needs, improving diagnostic support, and furthering therapeutic development efforts.